Developing Module to Teach and Learn Writing Self-Introducing at Senior High School - Ega Nur Fadillah; Wakhid Nashruddin; Ahmad Rifai (Syntax Corporation, 2022)
The importance of modules is developed in the learning process because the module can facilitate students in independent and face-to-face learning. The objective of this research was to find out the characteristics of teaching and learning module and to describe how module as learning media can support the development. This research using qualitative method with research design is Research and Development (D&R). The data collection techniques used in this research are interviews and questionnaires. The data analysis technique used for the interview the questionnaires are data reduction, data display, and conclusion drawing/verification. The steps of this research are need analysis, research planning, and develop a preliminary from of product. This research found that the characteristics of teaching and learning module based on aspects of module, teaching, learning, writing, self-introduction, and senior high school (adolescent). The form of the teaching and learning module is in accordance with product specifications based on respondents anwers and product is validated by an expert.